2007
DOI: 10.1021/jf070031e
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies Specific to Thermostable Proteins in Animal Blood

Abstract: Bovine plasma proteins are used as high-quality protein supplements in animal feed and as binders or colorants in food for human consumption. Religious observance, as well as recent fears of epidemic bovine spongiform encephalopathy, highlights the need for methods to detect bovine blood in processed food and animal feed for regulatory purposes, as the currently available methods are neither species-specific, blood-specific, nor valid for excessively heat-processed samples. This paper reports the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Nonfat dry milk (NFDM) was purchased from a local supermarket. The MAb, Bb1H9 used for this study, was raised against crude heated bovine blood protein extract as reported in our earlier studies (Hsieh and others 2007). …”
Section: Methodsmentioning
confidence: 99%
“…Nonfat dry milk (NFDM) was purchased from a local supermarket. The MAb, Bb1H9 used for this study, was raised against crude heated bovine blood protein extract as reported in our earlier studies (Hsieh and others 2007). …”
Section: Methodsmentioning
confidence: 99%
“…The assay did not react with any of the other nonblood proteins tested except for a weak crossreaction with nonfat dry milk. This weak cross-reaction with either MAb was not shown when an indirect ELISA format was used (15); this difference may be due to the much higher antigen Figure 1. Species specificity of sandwich ELISA using purified MAb Bb6G12 as the capture antibody and biotin-conjugated MAb Bb3D6 as the detection antibody.…”
Section: Resultsmentioning
confidence: 94%
“…The objective of this study was, therefore, to develop a reliable sandwich enzyme-linked immunosorbent assay (ELISA) using two monoclonal antibodies (MAbs), Bb6G12 and Bb3D6, previously obtained against bovine thermostable proteins (15), that is, bovine-specific to discriminate between bovine blood and blood from other species and tissue-specific to distinguish blood from nonblood tissue materials of bovine origin as well as proteins from other sources such as soy protein. The new assay is based on the recognition of a 60 kDa thermostable marker protein (analyte) that is able to withstand the heat treatment to which animal byproducts are routinely subjected.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported on a sandwich enzyme‐linked immunosorbent assay (sELISA) for the detection of bovine blood in animal feed that can be used for the surveillance of bovine spongiform encephalopathy (BSE), commonly known as mad cow disease (Ofori and Hsieh ). This assay utilizes 2 monoclonal antibodies (mAbs), Bb6G12 and Bb3D6, that recognize a 60‐kDa thermally stable antigenic protein in bovine blood (Hsieh and others ). This antigenic protein is likely to be present in the plasma fraction of blood because of its strong positive reaction with spray‐dried bovine plasma (Hsieh and others ; Ofori and Hsieh ).…”
Section: Introductionmentioning
confidence: 99%